Problematik Alat Peraga Kampanye: Penanganan Pelanggaran Pemilu dan Dampak Sampah Visual - Mazdan Maftukha Assyayuti; Aulia Rachman Eka Putra; Dandi Dwie Lisadi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Campaign props for the 2024 election are still problematic, one of which is against installations that are not in accordance with the rules. This study aims to analyze: first, handling violations against the installation of campaign props; second, the environmental impact due to the emergence of campaign props waste; and third, the regulation of campaign props in other democracies. Statute approach and comparative approach become methodological in this study. Based on the results of this study, first, the handling of alleged APK installation violations by Bawaslu is only limited to clearly regulated APKs which are then issued recommendations and suggestions for improvement. Secondly, the environmental impact of APK garbage includes various negative aspects that affect not only the cleanliness and beauty of the city, but also the sustainability of the environment more broadly. Third, restrictions are needed on the installation and procurement of APKs so that all election participants have equal fairness over space.